BIKE RENTAL LOCATION TRACKING SYSTEM WITH INTERNET OF THINGS IMPLEMENTATION - Fikri Hidayatulloh; Peby Wahyu Purnawan; Indra Riyanto; Nifty Fath; Suwasti Broto (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
The situation of bicycle rentals in the tourist spots of the old city, there is one bicycle rental company whose locations are scattered at several points in the old city, the bicycles used are ontel bicycles. Bike rentals are guarded by several people with the aim of maintaining bicycles. The design of a GPS system on bicycles that can be controlled through a hosting application, consists of two main parts, namely the design of the hardware to provide GPS on bicycles, through the hosting application and the software for the control system. The concept used for the process of granting gps is with two parts, namely Node and Gateway. The NEO 6M GPS module functions as a bicycle monitoring and is used for long-distance communication links. A system that has been comprehensively tested both in terms of accuracy and internet of things (IOT). Conduct GPS Tracker testing on bicycles in the Kota Tua area to find out how accurate the GPS Tracker is in determining the location of bicycles in the Kota Tua area. The test will produce the number of location points collected by the Neo 6M GPS while traveling in the Kota Tua area, the more point data collected, the better the precision and accuracy. The test results will also show bicycle trips in the Kota Tua area. From the results of an analysis of the Internet of Things on the GPS Tracker device, everything works well and is in line with expectations. Communication between the Sim 800L and Website Hosting has a delay. Making this system requires several components, such as Arduino Uno as the brain of the GPS Tracker device and also the GPS module. Neo 6M to get the coordinates from the satellite. For sending data to the server using the GPRS Sim 800L module, the system can display geofencing of the location of the bicycle on the monitoring map so that users can find out where the bicycle is even though the bicycle is rented out. The alert system can display notifications when the bicycle is outside the geofencing area